Albumin enhances PTX delivery ability of dextran NPs and therapeutic efficacy of PTX for colorectal cancer. Issue 22 (9th May 2019) - Zhang, Xinyu; Zhang, Ruhe; Huang, Jun; Luo, Moucheng; Chen, Xuewen; Kang, Yang; Wu, Jun
Abstract : The nanoassemblies of Dex6k –BSA–PTX and the pH-responsive drug release for anti-tumor applications in vivo . Abstract : To enhance the drug delivery capability of polysaccharides, a novel strategy was designed utilizing protein as a new party to assist the encapsulation and release of PTX. Herein, the BSA–PTX complex was first prepared, and aldehyde-dextran was then successfully cross-linked with BSA–PTX to obtain pH-sensitive Dex6k –BSA–PTX nanoparticles via the Schiff base reaction. With a size of 150 nm and high drug loading, the Dex6k –BSA–PTX NPs significantly prolonged the blood half-life of PTX and could be passively targeted to tumor tissues, with a significant inhibition of the growth of tumor cells in vivo and in vitro .